MGM 551 - Operations Research (September 2003) - PPSM, Pusat Pengajian Sains Matematik (2003)
UNIVERSITI SAINS MALAYSIA First Semester Examination Academic Year 2003/2004 September 2003 MGM 551 - Operations Research Time : 3 hours Please ensure that this exam paper consists of FOUR [4] printed pages before you begin the exam. Answer all FIVE questions.